PENGARUH GAYA KEPEMIMPINAN DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA DINAS CIPTA KARYA DAN TATA RUANG KOTA TANGERANG SELATAN - Nur Fadhilah; Sri Sukapti (Journal of Research and Publication Innovation, 2025)
The purpose of this research is to determine the effect of Leadership Style and Work Discipline on Employee Performance at the Cipta Karya and Spatial Planning Office of South Tangerang City. The population in this study were employees of the Cipta Karya and Spatial Planning Office totaling 68 people with a sample size of 68  people. The method used in this research is quantitative descriptive method with associative approach. The technique used is sampling technique with probability sampling method, the sampling method uses slovin theory. The analysis used is regression analysis, correlation coefficient analysis, coefficient of determination analysis and hypothesis testing. The results of this study are Leadership Style (X₁) and Work Discipline (X₂) have a significant and positive effect on Employee Performance (Y) with the results of the regression equation Y = 3,690 + 0.166X₁ + 0.781X₂. The correlation coefficient shows a strong relationship with a correlation value of 0.803. The coefficient of determination simultaneously affects 0.634 with a percentage value of 63.4%. Simultaneous hypothesis testing of Leadership Style (X₁) and Work Discipline (X₂) on Employee Performance (Y) obtained the results of F count> F table or 34.297> 3.1, then H0 is rejected and H3 is accepted. This means that there is a simultaneous significant influence between Leadership Style (X₁) and Work Discipline (X₂) on Employee Performance (Y).